Cellular handling of protein aggregates by disaggregation machines - Mogk, Axel; Bukau, Bernd; Kampinga, Harm H. (Molecular cell, 2018)
Both acute proteotoxic stresses that unfold proteins and expression of disease-causing mutant proteins that expose aggregation-prone regions can promote protein aggregation. Protein aggregates can interfere with cellular processes and deplete factors crucial for protein homeostasis. To cope with these challenges, cells are equipped with diverse folding and degradation activities to rescue or eliminate aggregated proteins. Here, we review the different chaperone disaggregation machines and their mechanisms of action. In all these machines, the coating of protein aggregates by Hsp70 chaperones represents the conserved, initializing step. In bacteria, fungi, and plants, Hsp70 recruits and activates Hsp100 disaggregases to extract aggregated proteins. In the cytosol of metazoa, Hsp70 is empowered by a specific cast of J-protein and Hsp110 co-chaperones allowing for standalone disaggregation activity. Both types of disaggregation machines are supported by small Hsps that sequester misfolded proteins.